Student Involvement as Participatory Supervisors Accompanying the Development of Democratic Development (Law Research Review Quarterly, 2018)
The presence of participatory supervision rather than active citizens is, of course, highly expected to be carried out in an honest and fair election without partiality for either candidate pair for the election. EThis study aims to find out how appropriate supervision assistance is carried out by students in organizing the 2019 legislative and presidential and vice presidential elections in the city of Magelang as well as to find out and analyze the form of supervision assistance conducted by students whether it can be effective and efficient for the continuation of legislative elections and presidential and vice presidential elections during the development of democratic system development. This research was conducted normatively which prioritized literature study with primary data base and supported by secondary data based on data from the field by conducting direct interviews with informants relating to the problems in this study. The results of research in the form of supervision assistance that is appropriate to do is with the involvement of students starting at the time of data collection, registration, determination of the final voter list, voting and during vote counting, so that it will be well backuped at each stage of the process that can prevent election violations and the involvement of students as a companion.